Assessment of damper performance in controlling cable vibrations using a reliability-based framework. (2017) - Mohammadi, Seyed Ali; Cheng, Shaohong; Ghrib, Faouzi
Owing to their long flexible nature and low intrinsic damping, bridge stay cables are prone to various types of wind-induced vibrations, among which the rain-wind-induced vibration is most frequently observed on site. External dampers are widely used to control such unfavourable cable oscillations and their effectiveness in suppressing large-amplitude cable vibrations was addressed in many studies using deterministic approaches. However, the mechanical and/or physical properties of cables and the attached dampers could not only deviate from their respective nominal design values at a given design point, but also vary considerably during the lifetime of a cable-stayed bridge and thus affect damper efficiency. Hence, for a realistic damper performance assessment, these uncertainties should be taken into account. The objective of this paper is to present a time-variant reliability-based framework model to assess how uncertainties in the structural parameters of a cable-damper system would influence the time specific reliability performance of an external damper yielded from the current design practice.